Peran Guru Bimbingan Konseling Dalam Kegiatan Kunjungan Rumah Pada Pembelajaran Daring - Ria Hayati; Rama Fadli (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2022)
During a pandemic, various activities must be carried out online. This also affects the role of the guidance and counseling teacher services. BK teachers themselves have an important role to play in distance learning during the pandemic. The role and presence of Guidance and Counseling (BK) teachers in the current pandemic is very much needed by students as a place to vent or share related to distance learning. Counselor must still be able to provide services to their foster students even though they are through Remote Services or what is commonly called LJJ. The role of counseling teachers in LJJ is very important so that students can develop optimally in accordance with their development tasks. Therefore, moving on from this problem, I tried the role of the counselor in conducting home visit services in the era of the Covid 19 pandemic.